A QUALITATIVE STUDY ON CULTURAL MEDIATIONS IN 2018 PRESIDENTIAL ELECTIONS VOTERS IN BRAZIL - Silva, Priscila Kalinke; Amorin, Gabriela Ribeiro [UNESP] (Univ Fundacao Mineira Educacao & Cultura-fumec, 2020)
This research aims to analyze the processes of cultural mediations through the study of this theory and analysis of a qualitative research with female voters of Jair Bolsonaro and Fernando Haddad, in the second round of the 2018 presidential elections, in Brazil. The theoretical-methodological framework is based mainly on the mediation studies by Martin-Barbero and Orozco. For data collection, focus groups and / or interviews were conducted with a total of 10 women in order to understand the categories created for analysis. It was possible to identify substantial differences regarding referential and institutional mediations between the two groups of voters.
Keywords: Cultural Mediations; Presidential Elections 2018; Women Voters